THE EXPANDING EARTH DALAM PERSPEKTIF AL-QUR'AN - Nada Mohammad, Shafwatun; Ahmad Nurrohim; Aisyah, Septi (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study examines the relationship between the concept of the expansion of the earth from the perspective of the Qur'an and modern geological theory, especially regarding the movement of the earth's plates influenced by mantle convection. This study highlights the importance of understanding the expansion of the earth from both a scientific and spiritual perspective by analyzing terms in the Qur'an, such as madda, firasya, and daha. This study uses a qualitative approach through a literature study, integrating scientific literature and religious texts. The results of the study show that although there are differences between the concept of